LITHOSPHERIC AND SUBLITHOSPHERIC ANISOTROPY BENEATH THE BALTIC SHIELD FROM SURFACE-WAVE ARRAY ANALYSIS - Pedersen H.A.; Bruneton M.; Maupin V. (My University, 2006)
We report measurements of radial and azimuthal anisotropy in the upper mantle beneath southern and central Finland, which we obtained by array analysis of fundamental-mode Rayleigh and Love waves. Azimuthally averaged phase velocities were analysed in the period range 15 to 190 s for Rayleigh waves and 15 to 100 s for Love waves. The azimuthal variation of the Rayleigh wave phase velocities was obtained in the period range 20 to 100 s. The limited depth resolution of fundamental-mode surface waves necessitated strong damping constraints in the inversion for anisotropic parameters. We investigated the effects of non-unicity on the final model by experimenting with varying model geometries. The radial anisotropy beneath Finland can be explained by a lithosphere at least 200 km thick, predominantly (> 50% by volume) composed of olivine crystals having their a-axes randomly distributed in the horizontal plane. On the contrary, the measured lithospheric azimuthal anisotropy is small. This can be reconciled with body-wave observations made in the area that indicate a complex pattern of rapidly varying anisotropy. Below 200-250 km depth, that is below the petrologic lithosphere as revealed by xenolith analyses conducted in the area, the magnitude of the azimuthal anisotropy increases and would be compatible with a mantle containing 15-20% by volume of olivine crystals whose a-axes are coherently aligned in the N-NE direction. The alignment of the a-axes is off the direction of present-day absolute plate motion in either the no-net-rotation or hot-spot reference frame, currently N55-N60. We interpret this mismatch as evidence for a complex convective flow pattern of the mantle beneath the shield, which, by inference, is decoupled from the overlying lithosphere. © 2006 Elsevier B.V. All rights reserved.
Keywords: ANISOTROPY; BALTIC SHIELD; CONTINENTAL LITHOSPHERE; SURFACE-WAVES